Evaluation of child protection case in Indonesia: Exploring barriers and policy directions - Werang, Nicolaus Petrus Likuwatan; Werang, Maria Lusiana Florentin (Journal of Gender Equality Disability Social Inclusion and Children, 2026)
Background: Indonesia has built a strong legal foundation for child protection, including Law No. 35 of 2014 and the Convention on the Rights of the Child, which comprehensively regulates child protection. On the other hand, there is a significant gap between legal recognition and practical concretization, which the government actualizes through the Indonesian Child Protection Commission. Methods: This study employed a descriptive qualitative method with content analysis, collecting secondary data from 2016–2024. Data were organized, analyzed, and triangulated to examine child protection cases in Indonesia, providing insights to guide policy recommendations and address structural and coordination challenges. Findings: The findings reveal institutional crumble, limited coordination between central and regional governments, a lack of trained personnel, and weak data systems as the main issues in child protection cases in Indonesia. Despite policy and budgetary interventions, legal gaps, fragmented monitoring, and cultural barriers persist, highlighting the need for harmonized regulations, capacity building, integrated data, and community engagement to strengthen child protection. Conclusion: The study concludes that legal frameworks alone are insufficient; effective child protection requires coordinated institutions, stronger local capacity, cultural transformation, and a community-based approach to ensure children’s rights are fulfilled, upholding commitments and safeguarding every child consistently. Novelty/Originality of this article: The novelty of this study highlights the scientific implications of child protection cases in Indonesia by evaluating the period from 2016 to 2024 as a reflection to protect children’s rights, providing new insights to overcome barriers, and offering policy recommendations to adequately address these issues.